An experimental community: the East India Company in London, 1600–1800. Issue 2 (14th June 2019) - WINTERBOTTOM, ANNA
Abstract: The early East India Company (EIC) had a profound effect on London, filling the British capital with new things, ideas and people; altering its streets; and introducing exotic plants and animals. Company commodities – from saltpetre to tea to opium – were natural products and the EIC sought throughout the period to understand how to produce and control them. In doing so, the company amassed information, designed experiments and drew on the expertise of people in the settlements and of individuals and institutions in London. Frequent collaborators in London included the Royal Society and the Society of Apothecaries. Seeking success in the settlements and patronage in London, company servants amassed large amounts of data concerning natural objects and artificial practices. Throughout the seventeenth and eighteenth centuries, company scholars and their supporters in London sought to counter critiques of the EIC by demonstrating the utility to the nation of the objects and ideas they brought home. The EIC transformed itself several times between 1600 and 1800. Nonetheless, throughout the seventeenth and eighteenth centuries, its knowledge culture was characterized by reliance on informal networks that linked the settlements with one another and with London.